Nutritional Value of Cheese Stick Substituted with Fish Protein Hydrolysate as an Alternative Snack for School-Aged Children - Zulfa, Fairuz; Syauqy, Ahmad; Anjani, Gemala; Ayustaningwarno, Fitriyono; Rusyanto, Widya; Afifah, Diana Nur (Media Gizi Indonesia, 2026)
The health of primary school-aged children is a vital component of national development and is significantly influenced by adequate protein intake. This study aimed to create a nutritious cheese stick snack by replacing wheat flour with fish protein hydrolysate (FPH) flour. This experimental study used a completely randomized design with three formulations: F1 (59% wheat flour: 41% FPH flour), F2 (54% wheat flour: 46% FPH flour), and F3 (48% wheat flour: 52% FPH flour). The ingredients include wheat flour, FPH flour, soy protein isolate, margarine, cheddar cheese, and water. Nutritional, chemical, and amino acid profiles were analyzed using standard methods (Kjeldahl, Soxhlet, and HPLC), and statistical analysis was conducted using One-Way ANOVA followed by post hoc tests. The results indicated that formulation F3 had the highest levels of amino acids, including glutamate (19,375.6 mg/kg), aspartate (6,663.8 mg/kg), and leucine (5,992.2 mg/kg), all of which were statistically significant (p<0.05). However, the total protein content was not significantly different (p=0.399). Additionally, F3 had the lowest fat content (26.3%) and highest moisture level (7.8%), which may have affected the texture of the product. These findings suggest that F3 is the most nutritionally advantageous formulation and could serve as a healthy snack option for school-aged children. Future studies are recommended to optimize the product texture and structure through adjustments in formulation and processing methods, as well as to assess consumer acceptability for potential commercialization.